Educational Attainment and Cohort Size - Stapleton, David C.; Young, Douglas J. (Journal of Labor Economics, 1988)
"We argue that the postwar baby boom [in the United States] caused substantial fluctuations in both the economic rewards to education and educational attainment over the last 3 decades. If substitutability between young and old workers diminishes with education, the present value of lifetime earnings for a boom cohort is depressed more for highly educated workers, reducing incentives for educational attainment. The opposite is true for pre- and postboom cohorts. The diminishing substitutability hypothesis explains the declines in both the returns to college and college completion rates in the 1970s and predicts a substantial increase in educational attainment for postboomers."